A criminologia entre a biologia e a educação: o discurso sobre o psicológico na revista da Faculdade de Direito da Universidade Federal de Minas Gerais (1892-1962) - Erika Lourenco (2007)
The purpose of this dissertation is to describe the discourses about human subjectivity, here also named as psychological, appropriated and diffused by the Federal University of Minas Gerais Law School journal between 1892 and 1962, and to investigate the relationship between those discourses and the trends in psychology produced in Minas Gerais and in Brazil at that period. This Law School, one of the first to be founded in Brazil, is chosen for its role in the diffusion of psychological approaches to human mind in the first decades of the 20th century, side by side with teacher training schools then established. The relationship between different conceptions of human psyche, the education of lawyers and the evolution of the countrys juridical structure have not yet been fully investigated, notwithstanding its importance for present debates concerning the humanization of the juridical system and the possibilities of education in the prevention of criminal behavior. The theoretical reference that guided the research is the program of scientific studies proposed by Bruno Latour. This program aims at overcoming the debate internalism-externalism in the historiography of science, and considers that the immersion of scientists in their social and cultural context cannot be separated from their conceptual constructions. The questions proposed to scientists, the groups of individuals involved in the search for answers to those questions, their allied and funding institutions, the public representations of science are the factors that interact for the final production of scientific theories and research. The main source of information is the periodical(Law School Journal). Articles whose themes are related to Penal Law and Criminology were selected and, subsequently, the articles that are referred to psychology were chosen. The analysis of these articles has revealed that three categories of discourse about psychology have emerged sequentially in this Law School. In the first moment, the discourses aimed at the defense of the Positive School of Penal Law and Criminology prevailed. In this approach, the behavior of individuals was conceived as being determined by biology, and, therefore, their criminal behavior could be attributed to biological (innate) determinants. In the second moment, the discourses were marked by the presence of the psychometric approach. This approach valued the possibility of obtaining scientific measures of psychological characteristics and, through them, of discovering the personality traces pertaining to different types of criminals. In the third moment the psychiatric approach prevailed in the discourses concerning the psychological, aiming at, on one side, the understanding of the behavior of mad criminals, and, on the other side, to defend the prevention of crimes, be it through the education of childhood or the reeducation of criminals. Along the period investigated, these three trends were present in the discourses, however an organicist approach prevailed in the explanation of crime. Only in the beginning of the 1960s this approach began to be overcome, and education began to be considered a powerful means to prevent crime. The analysis of these three different lines of discourse shows that the Law School faculty participated in the process of construction and circulation of psychological knowledge in Minas Gerais, through the appropriation of concepts and theories in psychology that circulated in each moment, using them as a means of understanding the behavior of criminals. Besides, they contributed in the broadening, transformation and spreading of such information.